2008
DOI: 10.1007/s12253-008-9017-0
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation of Childhood Acute Lymphoblastic Leukaemia is Different Between Girls and Boys

Abstract: The aim of this study was to investigate seasonal trends in the incidence of acute lymphoblastic leukaemia (ALL) around the times of birth and diagnosis in children aged 0-4 years and also to examine gender specific effects. Children born in South Hungary during 1981-1997 were analysed. Registrations of first malignancies for children, diagnosed under age 5 years before the end of 2002 were obtained from the Hungarian Paediatric Oncology Group providing a representative sample of Hungarian children over a 17 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 22 publications
(23 reference statements)
3
13
0
Order By: Relevance
“…3), indicating that seasonality may affect the morbidity of ALL. However, controversy remains over the effect of seasonal factors in the incidence, diagnosis and treatment of ALL (7,24,29). Gao et al (12) performed an international survey in Singapore, the USA and Sweden to provide evidence for the seasonal diagnosis of ALL.…”
Section: Discussionmentioning
confidence: 99%
“…3), indicating that seasonality may affect the morbidity of ALL. However, controversy remains over the effect of seasonal factors in the incidence, diagnosis and treatment of ALL (7,24,29). Gao et al (12) performed an international survey in Singapore, the USA and Sweden to provide evidence for the seasonal diagnosis of ALL.…”
Section: Discussionmentioning
confidence: 99%
“…Four studies have suggested seasonal variation in births for leukemia, and three of the four have suggested that the birth peak occurs in late winter or spring(February (26), March (27), and April(28)), while the fourth suggested two distinct peaks in February and August(29). The variation seen in previous studies may be due to variations between community burden of infections between countries or variation in timing of infection seasons from year to year.…”
Section: Discussionmentioning
confidence: 99%
“…Infectious etiologies have been hypothesized for both ALL and AML (9) because of the high incidence of these cancers in early childhood, coinciding with common early infections and immune system immaturity (10). This hypothesis has been supported for ALL by some (1115) but not all (16–18) studies reporting associations with season of birth, a proxy for perinatal infectious exposures. However, season of birth has rarely been studied in relation to AML risk, and has never been examined in large population-based cohort studies with the potential to provide more robust and generalizable risk estimates.…”
Section: Introductionmentioning
confidence: 99%